Artikel Review : Efektivitas dan Keamanan Berbagai Rute Pemberian Obat Injeksi Suspensi - Dila Alvia Rahmasari; Maulina Apriani; Amina Syifa; Dewi Febiyanti; Nurul Islami Ningtiyas; Nabilla Navyani Putry A; Dewi Rahmawati; Dzakiya Zhihrotulwida; M.Fithrul Mubarok (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Advances in technology and research in the field of pharmacy have driven innovation in drug formulation and administration methods to improve the effectiveness and safety of therapy. One of the most widely developed dosage forms is suspension injections, which are sterile preparations containing particles of active ingredients that are insoluble in the carrier fluid. This study aims to review the effects of various administration routes, such as intra-articular, intramuscular, and subcutaneous, on the efficacy and safety of suspension injections. The method used is a literature study analyzing various scientific journals from databases published in the last ten years. The results of the review show that the route of administration has a significant effect on the therapeutic effect, where the intra-articular route provides a strong local effect with low systemic risk, the intramuscular route produces long-term effects and is relatively easy to perform, while the subcutaneous route provides stable drug release over a long period of time. Overall, the choice of injection route for suspension injections should be tailored to the characteristics of the drug, the patient's condition, and the therapeutic goals to achieve optimal, safe, and comfortable treatment outcomes for the patient.